2021
DOI: 10.1002/adma.202007733
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Intermetallic Pd3Bi for Efficient Electrochemical Nitrogen Reduction

Abstract: Electrocatalytic nitrogen reduction at ambient temperature is a green technology for artificial nitrogen fixation but greatly challenging with low yield and poor selectivity. Here, a nanoporous ordered intermetallic Pd3Bi prepared by converting chemically etched nanoporous PdBi2 exhibits efficient electrocatalytic nitrogen reduction under ambient conditions. The resulting nanoporous intermetallic Pd3Bi can achieve high activity and selectivity with an NH3 yield rate of 59.05 ± 2.27 µg h−1 mgcat−1 and a Faradai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(96 citation statements)
references
References 49 publications
4
87
0
Order By: Relevance
“…The fact indicates high NH 3 yield of NO 3 − ‐RR at PA‐RhCu cNCs originates from the KNO 3 electroreduction rather than N‐containing pollution species in the experimental environment. [ 55,56 ] Furthermore, it is observed that the NH 3 yield and faradaic efficiency of NH 3 for NO 3 − ‐RR at PA‐RhCu cNCs at 0.05 V applied potential are much higher than most reported values at various electrocatalysts (Table S1, Supporting Information), [ 29,44–52 ] proving the high NO 3 − ‐RR activity of PA‐RhCu cNCs. Obviously, the high apparent NO 3 − ‐RR activity of PA‐RhCu cNCs directly benefits from the high ECASA derived from the unusual frame‐like concave nanocube structure with hollow, pore‐like and dendritic features.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The fact indicates high NH 3 yield of NO 3 − ‐RR at PA‐RhCu cNCs originates from the KNO 3 electroreduction rather than N‐containing pollution species in the experimental environment. [ 55,56 ] Furthermore, it is observed that the NH 3 yield and faradaic efficiency of NH 3 for NO 3 − ‐RR at PA‐RhCu cNCs at 0.05 V applied potential are much higher than most reported values at various electrocatalysts (Table S1, Supporting Information), [ 29,44–52 ] proving the high NO 3 − ‐RR activity of PA‐RhCu cNCs. Obviously, the high apparent NO 3 − ‐RR activity of PA‐RhCu cNCs directly benefits from the high ECASA derived from the unusual frame‐like concave nanocube structure with hollow, pore‐like and dendritic features.…”
Section: Resultsmentioning
confidence: 89%
“…− -RR at PA-RhCu cNCs originates from the KNO 3 electroreduction rather than N-containing pollution species in the experimental environment. [55,56] Furthermore, it is observed that the NH 3 yield and faradaic efficiency of NH 3 for NO 3…”
Section: − -Rr Activity Of Pa-rhcu Cncs In Three Electrode Systemmentioning
confidence: 99%
“…Currently, the vast majority of works focus on the design of catalysts with special structures and compositions to improve NH 3 activity and selectivity, such as introducing doping heteroatoms or atomic vacancies, adopting supporters with low HER activity. [ 8,14–20 ] Nonetheless, such strategies for achieving efficient catalysts with both high activity and selectivity are rather challenging. [ 10,14,21,22 ] In terms of aqueous electrolytes, the proton‐poor neutral/alkaline solutions are generally used to lower the H + accessibility for a suppressed HER, [ 23–27 ] but they cannot broaden the potential gap between NRR and HER (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia is an essential platform chemical to the global economy and plays key roles in industry, agriculture and pharmaceutical chemistry. [1][2][3][4] It is also a preferred carbon neutral energy carrier for sustainable energy storage with a 17.6 wt% hydrogen content and a high energy density of 4.3 kW h -1 . [5][6][7] Dinitrogen reduction for ammonia is a vital step in the natural nitrogen cycle.…”
Section: Introductionmentioning
confidence: 99%